ANNUAL RAINFALL TREND AND THE NUMBER OF DAYS WITH RAIN IN THE MUNICIPALITY OF ALTO PIQUIRI- PR THROUGH THE MANN KENDALL TEST - Baldo, Maria Cleide; Tommaselli, Jose Tadeu Garcia [UNESP]; Kawahara, Luiz Felipe Yuiti; Numai, Alessandra Arissa (Univ Estadual Paulista Julio Mesquita Filho, 2021)
Rainfall is one of the most studied meteorological variables for both excess and lack can lead to several disturbances. The aim of this study consisted in analyzing the predominant patterns of temporal distribution of daily, monthly, seasonal and annual precipitation in the period 1976 to 2019 in the municipality of Alto Piquiri-PR. We also sought to verify the presence of significant trends in the total annual precipitation series and the total number of days with rainfall occurrence by means of the non-parametric Mann (1945) and Kendall (1975) test. The results obtained pointed out that the average annual rainfall was 1651 mm, while the anomalous rainy years were 1982, 1983, 2015 and 2016, and the dry one in 1991. The average number of rainy days came to 90 and the spring has recorded the highest rainfall heights. Almost all absolute monthly highs were recorded in the twelve wettest years of the entire period. No trend was detected in the total annual rainfall, but in the number of days with rain there was a significant trend, that is, the rains have become more concentrated mainly as of the year 1999. Associating this trend to climate change would not be correct with just 44 years of data, in fact, it is implied that this is a variability which took place in a given period.
Keywords: Rainfall; Rainfall trend; Temporal variability